2019
DOI: 10.1016/j.immuni.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Treg Cells Promote the SREBP1-Dependent Metabolic Fitness of Tumor-Promoting Macrophages via Repression of CD8+ T Cell-Derived Interferon-γ

Abstract: Highlights d Treg cells shape the intratumoral immune landscape required for tumor immune evasion d Treg cells promote an M2-like TAM phenotype indirectly by suppressing CD8 + T cells d CD8 + T cell-derived IFNg blocks SREBP1-dependent fatty acid metabolism in TAMs d SREBP1 inhibition augments the efficacy of immune checkpoint blockade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
182
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(199 citation statements)
references
References 42 publications
2
182
1
Order By: Relevance
“…Among them, macrophages show the highest content in tumor tissues and most significant regulatory effect on tumors; these cells can promote the proliferation, invasion, and metastasis of tumor cells and induce tumor cells to develop immune tolerance. These cells are known as tumor-associated macrophages (TAMs) (most studies have suggested that TAMs are mainly the macrophage M2 type) [46]. TAMs are often distributed around CSCs, and the amount of infiltration is closely related to the tumor histological grade and number of CSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, macrophages show the highest content in tumor tissues and most significant regulatory effect on tumors; these cells can promote the proliferation, invasion, and metastasis of tumor cells and induce tumor cells to develop immune tolerance. These cells are known as tumor-associated macrophages (TAMs) (most studies have suggested that TAMs are mainly the macrophage M2 type) [46]. TAMs are often distributed around CSCs, and the amount of infiltration is closely related to the tumor histological grade and number of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immune checkpoint molecule CD274 (PD-L1) was significantly up-regulated in the SCE_H subtype. This molecule suppresses the proliferation and differentiation of T lymphocytes, promotes the differentiation of Tregs, and induce the secretion of cytokines, thereby suppressing the immune response [46]. Prediction of the anti-PD-1 treatment response showed that SCE_H is more sensitive to anti-PD-1 than other subtypes, indicating that CD274 highly expressed in tumor/tumor stem cells and may be involved in the immune escape process of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, macrophages show the highest content in tumor tissues and had the most signi cant regulatory effect on tumors. These cells, which can promote the proliferation, invasion, and metastasis of tumor cells and induce tumor cells to develop immune tolerance, are known as tumor-associated macrophages (TAMs) (most studies have suggested that TAMs are primarily the M2 type) [57]. TAMs are often distributed around CSCs, and the amount of in ltration is closely correlated to the tumor histological grade and number of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immune checkpoint molecule, CD274 (PD-L1), was signi cantly upregulated in the SCE_H subtype. This molecule suppresses the proliferation and differentiation of T lymphocytes, promotes the differentiation of Tregs, and induce the secretion of cytokines, thereby suppressing the immune response [57]. Prediction of the anti-PD-1 treatment response showed that SCE_H is more sensitive to anti-PD-1 than other subtypes, indicating that CD274 is highly expressed in tumor / tumor stem cells and may be involved in the tumor immune escape process.…”
Section: Discussionmentioning
confidence: 99%
“…5). We find that on average our NIFA model performs better than NMF and ICA at this cell-type detection (Klein et al, 2015) inDrop Principal genes identified by PCA Silver Mouse: Embryonic Stem Cells 2,717 4 Kolodziejczyk (Kolodziejczyk et al, 2015) SMARTer Homogeneous cell line Gold Mouse: Embryonic Stem Cells 704 3 Li (Li et al, 2017) SMARTer Homogeneous cell line Gold Human: Colorectal Tumors 561 9 Liu (Liu et al, 2019) 10x drop-seq k-means clustering & specific markers Silver Mouse: Tumor immune cells 1,607 13 Nestorowa (Nestorowa et al, 2016) Smart-Seq2 hierachical clustering & specific markers Silver Mouse: Hematopoietic Stem Cells 1,656 9 Olsson (Olsson et al, 2016) SMARTer Flow cytometry & cell sorting Gold Mouse: Hematopoietic Stem Cells 382 4 SimKumar4easy (Duò et al, 2018) NA Simulated Gold NA 500 4 SimKumar4hard (Duò et al, 2018) NA Simulated Gold NA 499 4 SimKumar8hard (Duò et al, 2018) NA Simulated Gold NA 499 8 Zhengmix4eq (Duò et al, 2018) NA Simulated Gold NA 3,555 4 Zhengmix4uneq (Duò et al, 2018) NA Simulated Gold NA 6,414 4 Zhengmix8eq (Duò et al, 2018) NA Simulated Gold NA 3,971 8 Table 1. The complete set of datasets evaluated in this study.…”
Section: Cell-type Identificationmentioning
confidence: 98%